The effect of pedometer supported walking and telemonitoring after disc hernia surgery on pain, disability levels, and quality of life: study protocol - Aldemir, Kadriye; Gürkan, Aysel (International Journal of Clinical Trials, 2019)
Background: Surgical intervention is the most common among the methods used to treat LDH, and its success rate is high. Despite this, patients can experience mild to moderate pain and disability after surgery. In the management of this pain and disability, walking forms the first step of rehabilitation and is an easy and long term method. This study was planned to determine the effect of a pedometer supported walking program and telemonitoring after disc hernia surgery on pain, disability levels and quality of life. Methods: This study was planned as a randomized controlled study. Patients will be randomized into the study and control groups through the closed envelope method. Patients in the study group will receive an intervention through a 12 week walking program and weekly telemonitoring. The pain levels of the patients included in the study will be evaluated using the short form Mcgill pain questionnaire, their disability levels will be evaluated using the Oswestry disability index, and their quality of life will be evaluated using the SF-36. Patients in both the study and control groups will be evaluated with regard to pain and disability levels in the follow ups in the 3rd, 7th, and 11th weeks, and with regard to pain, disability, and quality of life in the 15th week. Conclusions: Daily regular walks have great importance in the management of mild lower back pain. This study was planned to determine the effect of walking with a pedometer after LDH surgery with weekly monitoring.